2020
DOI: 10.1093/hmg/ddz301
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic breast milk DNA methylation alterations in women who develop breast cancer

Abstract: Prior candidate gene studies have shown tumor suppressor DNA methylation in breast milk related with history of breast biopsy, an established risk factor for breast cancer. To further establish the utility of breast milk as a tissue-specific biospecimen for investigations of breast carcinogenesis, we measured genome-wide DNA methylation in breast milk from women with and without a diagnosis of breast cancer in two independent cohorts. DNA methylation was assessed using Illumina HumanMethylation450k in 87 breas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…In an analysis of single cell RNA-seq across human tissues, LMX1B was most highly expressed in salivary and breast glandular cells 56 . In addition, hypomethylation at a CpG island in LMX1B in human milk samples was associated with subsequent diagnosis of breast cancer in an epigenome-wide association study 57 , suggesting higher expression correlated with breast cancer risk, which is concordant with the direction of effect in our results. We also show that milk eQTLs can be leveraged to understand the effects of milk gene expression on the breastfed infant.…”
Section: Maternal Genotype and Milk Gene Expression Is Associated Wit...supporting
confidence: 87%
“…In an analysis of single cell RNA-seq across human tissues, LMX1B was most highly expressed in salivary and breast glandular cells 56 . In addition, hypomethylation at a CpG island in LMX1B in human milk samples was associated with subsequent diagnosis of breast cancer in an epigenome-wide association study 57 , suggesting higher expression correlated with breast cancer risk, which is concordant with the direction of effect in our results. We also show that milk eQTLs can be leveraged to understand the effects of milk gene expression on the breastfed infant.…”
Section: Maternal Genotype and Milk Gene Expression Is Associated Wit...supporting
confidence: 87%
“…There is no clinically useful, noninvasive biomarker for early detection of breast cancer. Previous studies reported that the circulating cell-free DNA-based epigenetic assay can detect early breast cancer; however, most previous studies used a smaller plasma sample size [ 16 , 44 , 92 ], did not carry out clinical blood validation [ 46 , 93 ], carried out detection using nipple fluid, which was not easily available in most women [ 40 , 94 ], or used the higher-cost Illumina HumanMethylation450 BeadChip [ 46 , 93 , 95 ], which may be difficult to use as a universal method in the clinic. Evidence has shown that mammography and ultrasonography support the early diagnosis of breast cancer and reduced breast cancer mortality.…”
Section: Discussionmentioning
confidence: 99%
“…We will use the Infinium MethylationEPIC Kit (Illumina) to assess DNA methylation in epithelial cells from bilateral breastmilk samples collected at baseline and 20 weeks as described in a previous study [ 29 ].…”
Section: Methodsmentioning
confidence: 99%